Analyzing the socio-economic factors of adolescent malnutrition in Bangladesh using Best Worst Method - Tanzim Redwan; Md. Abdus Shabur (Discover Sustainability)
Abstract Adolescent malnutrition remains a critical public health challenge in Bangladesh, characterized by a dual burden of undernutrition and overnutrition. Despite national efforts to combat malnutrition, adolescents remain a vulnerable group with limited targeted interventions. This study employs the Best–Worst Method (BWM) to systematically identify and prioritize key socio-economic, cultural, and healthcare-related factors contributing to adolescent malnutrition. A panel of 16 experts, including nutritionists, public health researchers, and medical professionals specializing in adolescent health, provided expert judgments for the BWM analysis. The findings reveal that poverty and financial hardship (23.06%) ranked as the most critical determinant, followed by lack of nutrition education (12.23%), limited access to healthcare services (11.01%), and food insecurity (10.57%). The results also highlight urban–rural disparities, with urban adolescents facing higher risks of overnutrition due to increased consumption of processed foods and sedentary lifestyles, while rural adolescents suffer from undernutrition due to food scarcity and inadequate healthcare infrastructure. Gender inequality and cultural practices (6.02%) had a relatively lower impact compared to economic and healthcare-related determinants but were still relevant in rural food allocation disparities. Sensitivity analysis confirmed the robustness of these rankings, reinforcing the reliability of the findings. To address adolescent malnutrition effectively, this study recommends expanding poverty alleviation programs, integrating nutrition education into school curricula, and strengthening healthcare access for adolescents. These findings provide a structured, evidence-based framework for targeted policymaking and sustainable interventions aimed at mitigating adolescent malnutrition in Bangladesh.